Nutrient dynamics and microbial community response in macrophyte-dominated lakes: Implications for improved restoration strategies. (1st January 2023) - Ma, Shuai; Geng, Huanhuan; Yan, Changchun; Han, Xiaomin; Xu, Dan; Zhao, Furong; Blake, Ruth E.; Zhou, Beihai; Chen, Huilun; Yuan, Rongfang; Jin, Baoshi; Liu, Haijun; et al.
Abstract: Although lakes dominated by macrophytes are conducive to ecological balance, this balance is easily disrupted by excessive nutrients flowing into the lake. However, knowledge of whether excessive nutrients lead to different microbial environmental vulnerabilities in the lake sediment between macrophyte-dominated areas and macrophyte-free areas is a prerequisite for the implementation of targeted protection measures. In this study, we investigated bacterial communities in sediments using high-throughput sequencing of 16S rRNA genes. Our results showed that the sources of total nitrogen (TN) and organic matter (OM) were related to the macrophytes. The structure, drivers, and interspecific associations of bacterial community, which were more susceptible to increased changes in TN and OM, differed significantly between macrophyte-dominated areas and macrophyte-free areas. More precisely, the lake edge, where was occupied by macrophytes, had a higher proportion of deterministic phylogenetic turnover (88.89%) than other sites, as well as a wider ecological niche and a tighter network structure. Further, as the difference in TN increased, the main assembly processes in surface sediments changed from stochastic to deterministic. However, the majority of phyla from the lake edge showed a greater correlation with excessive nutrients, and the selection of the community by excessive nutrients was more obvious at the edge of the lake. In addition, our results demonstrated that the stability of the bacterial community in macrophyte-free areas is greater than in macrophyte-dominated areas, while an excessively high deterministic process ratio and nutrient (TN and OM) concentration significantly reduced bacterial community stability at macrophyte-dominated areas. Taken together, these results provide a better understanding of the effects of excessive nutrients derived from macrophytes on bacterial community patterns, and highlight the importance of avoiding the accumulation of TN and OM in macrophyte-dominated areas to enhance the sustainability of the ecosystem after restoration of lakes with macrophytes. Graphical abstract: Image 1 Highlights: TN and OM played important roles to impact the bacterial community. Differences in increasing TN drove the assembly process from stochastic to deterministic. The connectivity and stability of networks changed in the opposite direction from shore to the center of lake. TN has a stronger effect on the stability of bacterial communities on the edge of the lake.